ANALISIS PERAN GANDA PEREMPUAN GENERASI SANDWICH PADA RUANG PUBLIK DAN DOMESTIK DI KABUPATEN BATUBARA - Purba, Adinda Dilla Ayuningtyas; Susanti, Neila (Jurnal Ilmiah Sosiologi Agama (JISA), 2024)
This research examines the dual role of sandwich generation women in the public and domestic spheres. The sandwich generation here refers to individuals, especially women, who have to take care of their children while caring for their parents. So that sandwich generation women have a greater role in the family. The main purpose of this study is to describe the dual role of sandwich generation women and analyze how sandwich generation women balance their roles in the domestic and public spheres as well as the forms of dual roles carried out in everyday life. The research method used is qualitative method. Data were obtained through in-depth interviews and participatory observation with sandwich generation women in Batubara Regency. The results showed that the role of sandwich generation women in Batubara Regency has increased significantly. The dual roles experienced by sandwich generation women are reproductive, production and social roles. In the domestic space, they act as primary caregivers who provide physical and emotional needs for family members. Meanwhile, in the public sphere, they play an active role in the world of work and social activities, even as the main breadwinner. They carry out dual roles by balancing work and family responsibilities